(untitled) (International Journal of Environmental Sciences, 2025)
This study aims to examine the impact of business intelligence applications on overcoming barriers to decision support systems in Syrian firms operating in the information technology sector. The research focuses on Syrian firms registered with the Gaziantep Chamber of Commerce (totaling 525) in the Information Technology (IT) sector. A sample of 223 Syrian firms was surveyed. The findings are based on this sample, allowing for generalizability. The study evaluates the levels of barriers to decision support systems and the use of business intelligence in the IT sector among Syrian firms, based on the research model and collected data. A positive relationship between BI systems and decision support systems (DSS) has been hypothesized. Consequently, it was assumed that there is a correlation between perceptions of BI and DSS, leading to the development of Hypothesis 6. It was found that there is no perceptual difference between BI factors and participants’ gender, age, and tenure. Thus, it can be stated that BI is not influenced by gender, age, or tenure. However, a perceptual difference was identified between BI factors and participants’ educational levels and job titles. Therefore, it can be concluded that BI is influenced by the educational levels and job titles of the participants.